2009
DOI: 10.3390/v1030979
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Adaptive Immune Responses to Herpes Simplex Virus

Abstract: Immune responses against HSV-1 and HSV-2 are complex and involve a delicate interplay between innate signaling pathways and adaptive immune responses. The innate response to HSV involves the induction of type I IFN, whose role in protection against disease is well characterized in vitro and in vivo. Cell types such as NK cells and pDCs contribute to innate anti-HSV responses in vivo. Finally, the adaptive response includes both humoral and cellular components that play important roles in antiviral control and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 178 publications
(173 reference statements)
1
115
0
2
Order By: Relevance
“…iii) In principle, STING is a component of the host innate defenses against exogenous DNA, and its function has been linked to activation of IRF3 and NF-κB (13)(14)(15). Numerous studies have shown that wild-type HSV-1 is fully competent in blocking the activation of IRF3 and NF-κB (10,25,26). Nevertheless, it came as a surprise that wild-type HSV-1 replicated better in HEL cells that had been depleted of STING.…”
Section: Discussionmentioning
confidence: 99%
“…iii) In principle, STING is a component of the host innate defenses against exogenous DNA, and its function has been linked to activation of IRF3 and NF-κB (13)(14)(15). Numerous studies have shown that wild-type HSV-1 is fully competent in blocking the activation of IRF3 and NF-κB (10,25,26). Nevertheless, it came as a surprise that wild-type HSV-1 replicated better in HEL cells that had been depleted of STING.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate how commensal microbiota support immune protection against HSV-2 infection in the vaginal mucosa, we first explored the effect of commensal bacteria on the innate immune response. Innate immunity plays a pivotal role in limiting viral replication and initiating adaptive immunity in response to primary viral infection (16,17). Following vaginal mucosal HSV-2 infection, production of proinflammatory cytokines, such as IL-6, TNF-α, and IL-12p40, was not impaired in antibiotic-treated mice (Fig.…”
Section: Antibiotic Treatment Induces An Imbalance In Microbial Compomentioning
confidence: 97%
“…The T H 1 cells preferentially develop during infections by intracellular microorganisms, such as occurs in viral infections (Chew et al, 2009). It is generally accepted that T H 1 cells mainly produce IFNg and are responsible for propagating cell-mediated immunity (Wang & Fish, 2012).…”
Section: Discussionmentioning
confidence: 99%